Achievements and Drawbacks in Modern Researches of Club Activities - Zhalyuk, Oksana (Pedagogical Discourse, 2013)
The state of scientific development of modern problems of club activity in modern terms is analysed. The questions of theory, methodology and practice of scientific researches of wide range ofnationaleducational, socio-cultural, cultural and leisure activitiesof club establishments withdifferent categories of people are examined. The source basis of actual aspects of modern public cultural policy in the country and abroad, transformations of tendencies, principles, areas of club work of different patterns of ownership in the conditions of Ukrainian state creation and global changes in the world, their financial, resource and staffing problems are comprehensivelyexplained.